Behavior play therapy untuk meningkatkan atensi pada anak Attention Deficit Hyperactivity Disorder (ADHD) - Sari, Eka Nur Maulida; Suryaningrum, Cahyaning (Procedia : Studi Kasus dan Intervensi Psikologi, 2023)
Attention deﬁcit hyperactivity disorder (ADHD) is a neurological disorder in the form of behavior that is characterized by the development of an inappropriate level of attention and affects a person’s ability to organize and maintain attention on a task. In this case, the subject cannot focus, is unable to concentrate and difﬁcult to control. Based on the problems experienced, the most troubling current is the inattentive behavior of the subject who cannot focus when doing tasks. This was reported by parents and therapists. The assessment methods are interviews, observation, the Wechsler Intelligence Scale for Children (WISC), and the ADHD rating scale. The intervention given to overcome is behavior play therapy with beat the clock games. The results of the intervention show that inattentive behavior in the form of not being able to focus when doing tasks can be reduced. Keywords: Attention deﬁcit hyperactivity disorder, attention behavior play therapy, children Abstrak Attention deficit hyperactivity disorder (ADHD) merupakan masalah perilaku pada diri seseorang secara neurologis yang ditandai dengan perkembangan tingkat inatensi tidak sesuai dan mempengaruhi kemampuan seseorang untuk mengatur dan mempertahankan perhatian pada suatu tugas. Dalam studi kasus ini subjek tidak dapat fokus, kurang dapat berkonsentrasi dan sulit dikendalikan. Tujuan dari studi kasus ini adalah untuk meningkatkan atensi subjek yang tidak dapat fokus ketika mengerjakan tugas. Metode asesmen menggunakan wawancara, observasi, Wechsler Intelligence Scale for Children (WISC), dan ADHD rating scale. Intervensi yang diberikan untuk mengatasi masalah tersebut adalah behavior play therapy dengan permainan beat the clock. Hasil intervensi menunjukkan bahwa atensi dalam mengerjakan tugas dapat meningkat. Kata kunci: Attention deﬁcit hyperactivity disorder, attention behavior play therapy, anak